Human papillomavirus types in invasive cervical cancer worldwide: a meta-analysis - Gary M. Clifford; Jennifer S. Smith; Martyn Plummer; Núbia Muñóz; Silvia Franceschi (2003)
This study investigated regional variations in the contribution made by different human papilloma (HPV) types to invasive cervical cancer (ICC). A total of 85 studies using polymerase chain reaction to estimate HPV prevalence in ICC were identified. Data on HPV prevalence were extracted separately for squamous cell carcinoma (SCC) and for adeno- and adenosquamous-carcinoma (ADC). A total of 10 058 cases (8550 SCC, 1508 ADC) were included in pooled analyses. The most common HPV types in ICC were, in order of decreasing prevalence, HPV16, 18, 45, 31, 33, 58, 52, 35, 59, 56, 6, 51, 68, 39, 82, 73, 66 and 70. In SCC, HPV16 was the predominant type (46-63%) followed by HPV18 (10-14%), 45 (2-8%), 31 (2-7%) and 33 (3-5%) in all regions except Asia, where HPV types 58 (6%) and 52 (4%) were more frequently identified. In ADC, HPV prevalence was significantly lower (76.4%) than in SCC (87.3%), and HPV18 was the predominant type in every region (37-41%), followed by 16 (26-36%) and 45 (5-7%). The overall detection of HPV DNA was similar in different regions (83-89%). A majority of ICC was associated with HPV16 or 18 in all regions, but approximately a quarter of all ICC cases were associated with one of 16 other HPV types, their distribution varying by region.